Regional Economic Integration concept on South African construction industry: Lessons for other African construction industries - Bimbola, Akinrata Ebunoluwa (International Journal of Economics, 2016)
Purpose: Regional economic integration initiatives have been prospect of enhanced economic growth in South African construction industry. The impact of regional economic integration and globalization on construction industries in South Africa is evidenced by the decreasing market share of the local players in the industry. Developing countries need to institute radical reforms in their development agenda in order to leapfrog, and bridge this difference. That is why increase in foreign participation in construction activities in South Africa, cross border strategic alliances, technology transfer are some impact of Regional economic integration on the industry. The aim of this paper is to understand the term ' Regional economic integration ' and to study its impact on South African construction industry and the lessons to be learnt by other African construction industries. Its objectives include investigating the positive impacts on the Construction Industry, discussing the Regional economic integration in southern African i.e SACU and SADC; identifying the some lessons from it. Methodology: These will be briefly discussed mainly by exploring the literature and throwing light on the views of people who investigated and wrote in this field. Results: Region economic integration creates more profitable industries that demand skilled labour among South African construction industry. Wages are rising up and unemployment is getting less among skilled labour who managed to acquire skills in new technologies in different developing and advanced countries within the region. Policy recommendations: The paper ends with conclusions and recommendations, stressing the need for improvement on other construction industries in Africa participation in Regional economic integration, in related to lessons South African construction industry.